Can internet blogs be used as an effective advertising tool? The role of product blog type and brand awareness. Issue 3 (13th April 2015) - Ho, Chen-Hsun; Chiu, Kuang-Hui; Chen, Hsin; Papazafeiropoulou, Anastasia
Abstract : Purpose: – As blogs have become an important information communication medium, selecting blog types that are appropriate and effective for the products they are to promote is now an important issue in corporate advertising. However, the impact of different blog types on consumers and their advertising effectiveness are issues seldom addressed in the existing literature. The purpose of this paper is to view product information that consumers post on blogs as advertisements and compares advertising effectiveness between different blog types to help enterprises properly employ blogs in their marketing campaigns. Design/methodology/approach: – An experimental design was adopted, and 12 experimental contexts were designed. A valid sample of over 2, 000 responses was collected to study between-group differences in advertising effectiveness. Findings: – The analytical results showed between-group difference in advertising effectiveness, which indicated that blog advertising effectiveness varies with different combinations of product constructs and blog types. Research limitations/implications: – The limitations of this study related to the price factor was not incorporated into the experimental model, and shopping channels were not limited. There might be a gap between the prices of the experimental products and the average expense of online shoppers. Originality/value: – The study proposed a framework which can help enterprises to evaluate the type and brand awareness of a product to be promoted and to select the blog type that maximizes advertising effectiveness (perceived risk, ad attitude, brand attitude, and purchase intention) in diffusing product information.